A Multicenter Study of Recombinant Factor VIII (RecombinateTM) in Previously Treated Patients with Hemophilia A - White, G C, II; Courter, S; Bray, G L; Lee, M; The Recombinate Previously Treated Patient Study Group; Gomperts, E D (Thrombosis and Haemostasis, 1997)
A prospective, open-label multicenter investigation has been conducted to compare pharmacokinetic parameters of recombinant DNA-derived FVIII (rFVIII) and plasma-derived FVIII concentrate (pdFVIII) and to assess safety and efficacy of long-term home-treat- ment with rFVIII for subjects with hemophilia A. Following comparative in vivo pharmacokinetic studies, 69 patients with severe (n = 67) or moderate (n = 2) hemophilia A commenced a program of home treatment using rFVIII exclusively for prophylaxis and treatment of all bleeding episodes for a period of 1.0 to 5.7 years (median 3.7 years). The mean in vivo half-lives of rFVIII and pdFVIII were both 14.7 h. In vivo incremental recoveries at baseline were 2.40%/IU/kg and 2.47%/IU/kg, respectively (p = 0.59). The response to home treatment with rFVIII was categorized as good or excellent in 3,195 (91.2%) of 3,481 evaluated bleeding episodes. Thirteen patients received rFVIII for prophylaxis for twenty-four surgical procedures. In all cases, hemostasis was excellent. Adverse reactions were observed in only 13 of 13,591 (0.096%) infusions of rFVIII; none was serious. No patient developed an inhibitor to r FVIII.